2000
DOI: 10.1093/emboj/19.13.3366
|View full text |Cite
|
Sign up to set email alerts
|

The Nac2 gene of Chlamydomonas encodes a chloroplast TPR-like protein involved in psbD mRNA stability

Abstract: The psbD mRNA, which encodes the D2 reaction center polypeptide of photosystem II, is one of the most abundant chloroplast mRNAs. We have used genomic complementation to isolate the nuclear Nac2 gene, which is required for the stable accumulation of the psbD mRNA in Chlamydomonas reinhardtii. Nac2 encodes a hydrophilic polypeptide of 1385 amino acids with nine tetratricopeptide-like repeats (TPRs) in its C-terminal half. Cell fractionation studies indicate that the Nac2 protein is localized in the stromal comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
148
0

Year Published

2001
2001
2013
2013

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 152 publications
(155 citation statements)
references
References 64 publications
7
148
0
Order By: Relevance
“…Light/dark regulation of GUS transcript levels in Chlamydomonas chloroplast transformants carrying rbc L 59 end:GUS genes+ Transformants were grown in 12-h light/12-h dark cycles, total RNA was isolated at time points 11 h dark and 1 h light, and processed as described (legend to Fig+ 2; Materials and Methods)+ RNA gel blots were first hybridized to the atpB probe as a control and, after stripping of the membrane, to the GUS probe+ The increase upon illumination seen in abundance of transcripts of the endogenous atpB gene is due to increased transcription of the atpB gene in light and has been reported previously (Salvador et al+, 1993a)+ The membrane was exposed to X-ray film for 4 h for detection of atpB gene transcripts and for 24 h for detection of chimeric rbc L 59 end:GUS gene transcripts+ Numbers above the lanes denote nucleotide replacements in the rbc L 59 UTR sequence as depicted in Figures 1 and 2+ D: dark (also marked by a filled bar); L: light (also marked by an open bar)+ isolated by genomic complementation (Boudreau et al+, 2000)+ Putative cis-acting elements that are potential targets for RNA-stabilizing proteins have been localized in the 59 UTRs of chloroplast gene transcripts (Higgs et al+, 1999;Nickelsen et al+, 1999)+ A number of proteins were found in in vitro assays to bind to the 59 UTRs of Chlamydomonas chloroplast transcripts (Hauser et al+, 1996) and, in spinach, to the 59 UTRs of transcripts of genes that code for subunits of the ATP synthase complex (Hotchkiss & Hollingsworth, 1999)+ Although the identities and functions of these proteins have not been examined, it is possible that some of them are nucleus-encoded factors involved in mRNA stabilization+…”
Section: Discussionmentioning
confidence: 99%
“…Light/dark regulation of GUS transcript levels in Chlamydomonas chloroplast transformants carrying rbc L 59 end:GUS genes+ Transformants were grown in 12-h light/12-h dark cycles, total RNA was isolated at time points 11 h dark and 1 h light, and processed as described (legend to Fig+ 2; Materials and Methods)+ RNA gel blots were first hybridized to the atpB probe as a control and, after stripping of the membrane, to the GUS probe+ The increase upon illumination seen in abundance of transcripts of the endogenous atpB gene is due to increased transcription of the atpB gene in light and has been reported previously (Salvador et al+, 1993a)+ The membrane was exposed to X-ray film for 4 h for detection of atpB gene transcripts and for 24 h for detection of chimeric rbc L 59 end:GUS gene transcripts+ Numbers above the lanes denote nucleotide replacements in the rbc L 59 UTR sequence as depicted in Figures 1 and 2+ D: dark (also marked by a filled bar); L: light (also marked by an open bar)+ isolated by genomic complementation (Boudreau et al+, 2000)+ Putative cis-acting elements that are potential targets for RNA-stabilizing proteins have been localized in the 59 UTRs of chloroplast gene transcripts (Higgs et al+, 1999;Nickelsen et al+, 1999)+ A number of proteins were found in in vitro assays to bind to the 59 UTRs of Chlamydomonas chloroplast transcripts (Hauser et al+, 1996) and, in spinach, to the 59 UTRs of transcripts of genes that code for subunits of the ATP synthase complex (Hotchkiss & Hollingsworth, 1999)+ Although the identities and functions of these proteins have not been examined, it is possible that some of them are nucleus-encoded factors involved in mRNA stabilization+…”
Section: Discussionmentioning
confidence: 99%
“…Gumpel et al, 1995;Boudreau et al, 2000;Vaistij et al, 2000;Auchincloss et al, 2002;Dauvillee et al, 2003). However, in cases where PS1 suppressors have been recovered from PS2 strains or where a trait otherwise cannot be selected on minimal medium, recovery of the mutation requires other methods.…”
mentioning
confidence: 99%
“…Once RBP40-psbD mRNA complex formation has been established, Nac2 is released from the RNA. This transient interaction of the Nac2 complex with the psbD 5¢UTR is supported by the finding that Nac2 cannot be identified at polysomes from C. reinhardtii chloroplasts (Boudreau et al 2000). Afterwards, RBP40-mediated ribosomal assembly takes place and translation is initiated.…”
Section: Rbps Interacting With 5¢utrsmentioning
confidence: 68%
“…To date, three nuclear genes have been cloned from C. reinhardtii which encode proteins mediating their function via chloroplast 5¢UTRs. These include Nac2 and Mbb1, controlling the stabilization of psbD and psbB transcripts, respectively, and Tbc2, regulating translation initiation on the psbC mRNA (Boudreau et al 2000;Vaistij et al 2000b;Auchincloss et al 2002). Similar to the above-mentioned genetically defined factors involved in chloroplast-splicing, all three factors have been detected in highmolecular-weight complexes which also contain RNA; but it remains to be clarified whether or not they directly interact with their cognate transcripts.…”
Section: Rbps Interacting With 5¢utrsmentioning
confidence: 99%
See 1 more Smart Citation